1. ## rewrite equation

ok i have this y = 1 / (x - 1)

x = 1 / y + 1 / 1

can someone explain in steps?

2. Originally Posted by perpetual
ok i have this y = 1 / (x - 1)

x = 1 / y + 1 / 1

can someone explain in steps?
There are many ways to solve for x in something like this. (writing 1/1 is unnecessary AND unaesthetic)

One method:

$\displaystyle y = \frac {1}{x - 1}$ ..................multiply both sides by $\displaystyle x - 1$

$\displaystyle \Rightarrow (x - 1)y = 1$ ..........now divide both sides by $\displaystyle y$

$\displaystyle \Rightarrow x - 1 = \frac {1}{y}$ ..............now add 1 to both sides

$\displaystyle \Rightarrow x = \frac {1}{y} + 1$

3. lol yes i know im sorry it wasnt 1 / 1 its x = (1/(y) + 1) / 1

4. Originally Posted by perpetual
lol yes i know im sorry it wasnt 1 / 1 its x = (1/(y) + 1) / 1
that makes no difference, and is perhaps even more unaesthetic

anything divided by 1 is itself, so having the whole right side over 1 is useless

5. ..........now divide both sides by
ok guess at this point i dont understan why u dont distribute the y to(x-1)?

6. Originally Posted by perpetual
..........now divide both sides by
ok guess at this point i dont understan why u dont distribute the y to(x-1)?
that would be mixing x and y wouldn't it? our objective is to solve for x, thus we want to get x by itself on one side. distributing the y does not accomplish that

7. thanks for that and sorry about that extra post